EXPERIMENTAL INVESTIGATIONS OF THE HYDROTHERMAL GEOCHEMISTRY OF PLATINUM AND PALLADIUM: IV. THE STOICHIOMETRY OF PT(IV) AND PD(II) CHLORIDE COMPLEXES AT 100 TO 300°C - Gammons C.H. (My University, 1995)
A technique based on the common ion effect was used to obtain information on the stoichiometry of the Pt(IV) and Pd(II) chloride complexes at elevated temperature. The solubility of AgCl(s) was measured in solutions of fixed mHCl and varying ΣPt(IV) or ΣPd(II) concentration. Parallel experiments were conducted at Me/Cl mole ratios (Me = Pt or Pd) of 0.0-0.5 for mHCl = 0.03-3.0 at T = 100, 200, and 300°C. The average Cl ligand numbers for Pt ranged from 4.2 to 5.8, with the majority of values > 5. These results are adequately explained by a mixture of the simple monomeric species PtCl2-6, PtCl-5, and PtCl04. The temperature dependence of the equilibrium constant for the dissociation reaction PtCl2-6 = PtCl-5 + Cl- was obtained: log K = 2.40 (+/-0.25) -1278T , K (valid to 573 K), which is in good agreement with published low temperature data. The neutral PtCl04 species may become important at 300°C and low chloride concentrations (0.01 m HCl). Extrapolation of existing data indicates that the PT(IV) chloride complexes are stable with respect to Pt(II) chloride complexes over a range of fO2-pH conditions which narrows quickly with increase in temperature. Nonetheless, PtCl2-6 may be the dominant form of dissolved Pt in highly oxidized brines to at least 100°C. The average Cl ligand numbers for palladium ranged from 2.14 to 2.83, and were insensitive to temperature. These results could be explained by a mixture of PdCl2 and PdCl-3. However, this is in disagreement with published experimental data which indicate that PdCl-24 is the predominant form of aqueous Pd at high chloride concentrations. An alternate explanation is that a significant quantity of the total aqueous Pd was present as polynuclear complexes, due to the very high Pd/Cl ratios of the experiments. Insufficient data exist to discriminate between these two hypotheses.